Accounting Conservatism and Its Long Term Impact on Firm Valuation (gjstudies, 2018)
This research introduces a novel, cross-disciplinary framework for examining accounting conservatism by integrating principles from behavioral finance, information theory, and complex systems analysis—a significant departure from traditionalarchival accounting studies. We reconceptualize conservatism not merely as a staticreporting bias but as a dynamic information-processing mechanism that shapes afirm’s long-term strategic narrative and its interaction with capital markets. Thestudy’s originality lies in its methodological innovation: we develop a multi-layered,time-variant Conservatism Index (CI) that captures conditional, asymmetric recognition of gains versus losses, and we employ a longitudinal network analysis to modelhow conservatism propagates through a firm’s valuation ecosystem over extendedperiods. Our analysis of a unique, hand-collected dataset spanning 25 years forSP 500 firms reveals a non-linear, U-shaped relationship between accounting conservatism and long-term firm valuation, moderated by market sentiment regimesand industry volatility. Contrary to conventional wisdom suggesting a monotonicnegative impact due to earnings understatement, we find that moderate levels ofstrategic conservatism act as a signaling mechanism that reduces information asymmetry and builds reputational capital, thereby enhancing valuation in the long run.However, excessive conservatism leads to a ’credibility discount,’ where markets penalize firms for persistent under-reporting of economic reality. These findings offera fresh perspective on the valuation implications of conservative reporting, positioning it as a strategic tool rather than a mere compliance artifact, with significantimplications for standard-setters, managers, and investors seeking to understandthe long-term informational consequences of accounting choices.